2008
DOI: 10.1177/039463200802100119
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Lining Fluid Neutrophil-Gelatinase-Associated Lipocalin Levels in Premature Newborns with Bronchopulmonary Dysplasia and Patency of Ductus Arteriosus

Abstract: Patency of the ductus arteriosus (PDA) and bronchopulmonary dysplasia (BPD) development represent severe affections for premature newborns, therefore the research of early markers for these two conditions is really important. The aim of this study is to analyze epithelial lining fluid (ELF) Neutrophil-gelatinase-associated lipocalin (NGAL) levels for prediction of lung injury or possible involvement ofthis molecule in PDA. Only scarce and contrasting results have previously been published in this field. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…These authors also observed a correlation between high urinary NGAL levels and low gestational age. Capoluongo et al [17] found a significant correlation between NGAL concentrations in bronchopulmonary lavage and the presence of PDA. Using NGAL as a marker for the hemodynamic relevance of PDA, as done in our study, had not been addressed by these authors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These authors also observed a correlation between high urinary NGAL levels and low gestational age. Capoluongo et al [17] found a significant correlation between NGAL concentrations in bronchopulmonary lavage and the presence of PDA. Using NGAL as a marker for the hemodynamic relevance of PDA, as done in our study, had not been addressed by these authors.…”
Section: Discussionmentioning
confidence: 98%
“…NT-proBNP is supposed to represent a cardiac marker of hypoperfusion, H-FABP a potential marker of cardiac and intestinal hypoperfusion [15,16] . Increased levels of NGAL were hypothesized to indicate renal hypoperfusion as a result of a steal phenomenon caused by re-circulation of blood across an open duct, thus negatively affecting blood flow to the kidneys [12,17] .…”
Section: Introductionmentioning
confidence: 99%
“…NGAL levels in lung epithelial lining fluid were significantly higher in patients with patency of the ductus arteriosus and bronchopulmonary dysplasia, which provided a link of inflammation and angiogenetic processes in both pathologies [67]. Similarly, plasma NGAL was up-regulated in -thalassemia which might be due to the possible association of oxidative stress [68].…”
Section: Other Diseasesmentioning
confidence: 91%
“…74 Neutrophil-gelatinase-associated lipocalin (NGAL) included in a large macromolecular complex together with matrix metalloproteinase-9 (MMP-9), is considered a marker of infectious/inflammatory processes and induction of apoptosis. In a study by Capoluongo et al 75 , NGAL was increased both in infants developing BPD and in those with a patent ductus arteriosus (PDA) even after adjustment for possible confounders.…”
Section: Biomarkersmentioning
confidence: 98%